2018
DOI: 10.1007/s11936-018-0699-7
|View full text |Cite
|
Sign up to set email alerts
|

The Female Athlete’s Heart: Facts and Fallacies

Abstract: Purpose of the reviewFor many years, competitive sport has been dominated by men. Recent times have witnessed a significant increase in women participating in elite sports. As most studies investigated male athletes, with few reports on female counterparts, it is crucial to have a better understanding on physiological cardiac adaptation to exercise in female athletes, to distinguish normal phenotypes from potentially fatal cardiac diseases. This review reports on cardiac adaptation to exercise in females.Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 72 publications
1
41
0
1
Order By: Relevance
“…A characteristic, coherent distinction was observed regarding fibrosis and profibrotic factors: both control and exercised female rats showed significantly decreased collagen area and lower expression of TGFβ and MMP2 ( Figure 3 ). This is in line with previous observations, where women seem to be affected by atrial fibrillation, coronary atherosclerosis, and myocardial fibrosis less than male counterparts [ 39 ]. Indeed, there is evidence that estrogen receptors play a role in the regulation of collagen expression of cardiac fibroblasts [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…A characteristic, coherent distinction was observed regarding fibrosis and profibrotic factors: both control and exercised female rats showed significantly decreased collagen area and lower expression of TGFβ and MMP2 ( Figure 3 ). This is in line with previous observations, where women seem to be affected by atrial fibrillation, coronary atherosclerosis, and myocardial fibrosis less than male counterparts [ 39 ]. Indeed, there is evidence that estrogen receptors play a role in the regulation of collagen expression of cardiac fibroblasts [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…A recent review reported some mechanisms of cardiac remodelling and highlighted that hormones and genes may play a role in this process. 19 Some studies have shown the presence of androgenic and estrogenic receptors in myocytes and the hormonal effects on myocardial response. Whereas testosterone stimulates myocardial hypertrophy, estrogens inhibit the proliferation of cardiac fibroblasts.…”
Section: Where Is the Key?mentioning
confidence: 99%
“…There is evidence to suggest female cardiac adaptations may differ from those seen in their male counterparts. For example, females may be more likely to undergo concentric remodelling [ 20 , 21 ]. Studies that have demonstrated myocardial fibrosis have observed these adaptions only in their male participants [ 11 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest female cardiac adaptations may differ from those seen in their male counterparts. For example, females may be more likely to undergo concentric remodelling [20,21].…”
Section: Introductionmentioning
confidence: 99%